ANALYSIS OF BIOSECURITY CONTROL MEASURE POLICY IMPLEMENTATION ON HIGHLY PATHOGENIC AVIAN INFLUENZA IN JAKARTA - Iqbal, Muhammad; Nurmanaf, Rozany; Agustian, Adang (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2009)
Highly Pathogenic Avian Influenza (HPAI) was first detected inJakartain 2003 in which since that time, the virus has become pandemic in the area and has resulted in poultry and human deaths. Based on these facts, the provincial government ofJakartahas launched two policies on biosecurity control measure, namely Governor Legislation No. 15/2007 and Provincial Government Legislation No. 4/2007 in order to control raising poultry and its distribution in this area. It was implemented through field inspection towards free-range poultry, depopulation, stamping out, and poultry certification as well as planned poultry collection point and slaughter facility relocations. Nevertheless, certain reactions occurred which particularly derived from poultry business actors. Incomprehensive campaign and lack of community socioeconomic consideration were among the issues perceived as detrimental about the adopted policy. It therefore seems necessary to carry out participatory approach towards rearrangement concept to arrive at a comprehensive and holistic biosecurity control measure policy feedback.